Turog - Usi, Earl Joseph Nuarin 1993-; Usi, Earl Joseph Nuarin; Tolentino, Roland B.; University of the Philippines Diliman. College of Mass Communication (Quezon City University of the Philippines Diliman, 2015)
"Turog revolves around a day in Jess' life; a writer filled with regrets over the untimely death of his girlfriend, struggling to move on, recently have moved back in with his brother Mark at their old family house. As Mark leaves him alone for the day, Jess begins experiencing strange occurences that may be linked to the "Turog", a monster from a childhood tale that supposedly takes children away who refuse to take afternoon naps. The film utilizes the concept of the "monster as methaphor" and attempts to deconstruct what the monster stands for."
Vita.
Thesis
Keywords: Horror films; Monsters in motion pictures